Who should access germline genome sequencing? A mixed methods study of patient views. Issue 2 (26th November 2019) - Best, Megan C.; Butow, Phyllis; Jacobs, Chris; Savard, Jacqueline; Biesecker, Barbara; Ballinger, Mandy L.; Bartley, Nicci; Davies, Grace; Napier, Christine E.; Smit, Amelia K.; Thomas, David M.; Newson, Ainsley J.; et al.
Abstract: Implementation of any new medical test, including germline genome sequencing (GS) to inform cancer risk, should take place only when a test is effective, ethically justifiable and acceptable to a population. Little empirical evidence exists on patient views regarding GS for cancer risk. The aim of this study was to elicit opinions on who should be offered GS and who should pay for it. Participants with a probable genetic basis for their cancer (n = 335) and blood relatives (n = 199) were recruited to undergo GS and invited to complete questionnaires at baseline. A subset (n = 40) also participated in qualitative interviews about their views regarding access to GS to detect cancer risk. Our response rate was 92% for questionnaires and 100% for interviews. Participants expressed high enthusiasm overall for access to GS for those with a family history of cancer and anyone who requested testing, but enthusiasm was lower for universal access, if opting out was possible and finances not an issue. Rationales for these views reflected maximising the sound use of resources. Challenges to introducing community screening via GS to limit cancer burden were raised, including the current limits of science and individual ability to cope with uncertain results. Participants undergoing GS supported cancer risk testing for those with a family history of cancer but were concerned about the challenges of designing and implementing a population‐based GS cancer‐screening program. Abstract :